Use of Virtual Reality and Augmented Reality in International Arbitration - Vergara Olmos, Ricardo (Latin American Journal of Trade Policy, 2020)
The technological development has brought many changes in the way that the arbitral process takes place. This article analyzes the impact generated by the use of virtual reality and augmented reality for the production and evaluation of evidence, examining both the benefits and the possible problems that may arise by the implementation of such technology. Within its problems, this article deepens in the alteration of the arbitrator’s role caused by the immersive effect of virtual reality, in the replacement of the judge regarding the interpretation of the fact upon which the simulation is based, and in the costs of using these technologies in international arbitration. Finally, this article gives some recommendations in order to provide for a careful implementation of this technology in the arbitral process.